Two new species of Zetzellia Oudemans (Acari: Stigmaeidae) that threaten the concept of genera: Disgeneric marriage? - Hernandes, Fabio A. [UNESP]; Feres, Reinaldo J. F. [UNESP] (My University, 2005)
Two new species of Zetzellia Oudemans, Z. agistzellia sp. n. and Z. quasagistemas sp. n., are described from rubber trees of northwestern São Paulo State, Brazil. Females have clear features of Zetzellia, whereas males resemble Agistemus in some characters. Immatures are also described. The discovery of these species raises some problems concerning generic concepts in Stigmaeidae. Since features of different genera are present in the same species, the authors suggest that the scope of those genera should be reviewed. Copyright © 2005 Magnolia Press.
Keywords: Hevea brasiliensis; Predators; Systematics; Taxonomy; Zetzellia; Acari; Agistemus; Stigmaeidae